Development and testing of computer software for nursing assessment and care planning at a spinal cord injury center. - Lloyd EE; Toth LL; Rogers S (SCI Nursing, 1994)
This paper describes a pilot project using a Macintosh personal computer and customized software to computerize nursing admission assessment and care planning data. The project setting is a 47-bed Spinal Cord Injury Center with two inpatient units and an outpatient department serving approximately 1,000 patients with spinal cord injury at a Department of Veterans Affairs Medical Center in northern California. The computer software development, implementation, and evaluation are described. This software (MacNursing) was found to be a low cost, customized approach to computerizing spinal cord injury admission assessment data and care planning which reduces repetitive writing and facilitates continuity of care. Personal computers and this software have provided the mechanism for establishing a spinal cord injury patient database.